2023
DOI: 10.3390/ani13071146
|View full text |Cite
|
Sign up to set email alerts
|

Using Multivariate Adaptive Regression Splines to Estimate the Body Weight of Savanna Goats

Abstract: The Savanna goat breed is an indigenous goat breed in South Africa that is reared for meat production. Live body weight is an important tool for livestock management, selection and feeding. The use of multivariate adaptive regression splines (MARS) to predict the live body weight of Savanna goats remains poorly understood. The study was conducted to investigate the influence of linear body measurements on the body weight of Savanna goats using MARS. In total, 173 Savanna goats between the ages of two and five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The current correlation results further indicated highly statistical correlation between body weight and morphometric traits (Heart girth and body length). The results were in line with the results of other studies ([17]; [5]; [13]) who indicated a highly statistical correlation between body weight, heart girth and body length. The results means that by improving heart girth, body volume and body length will improve body weight of the Savanna goats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current correlation results further indicated highly statistical correlation between body weight and morphometric traits (Heart girth and body length). The results were in line with the results of other studies ([17]; [5]; [13]) who indicated a highly statistical correlation between body weight, heart girth and body length. The results means that by improving heart girth, body volume and body length will improve body weight of the Savanna goats.…”
Section: Discussionsupporting
confidence: 92%
“…The study was conducted at Game Breeder farm located in Bysteel, under Polokwane Local Municipality, South Africa. The area has an annual rainfall of 600 mm with summer temperature ranging from 16 to 28 degree Celsius and winter temperature ranging from 7 to 21 degrees Celsius [13].…”
Section: Study Areamentioning
confidence: 99%
“…The use of body weight estimation approach using linear body measurements is a broadly used phenomenon that determines the relationship between linear body morphometric traits in animals (Rashijane et al, 2023). The weak association between body weight and tail length in Karakul and Meat-master males found in the current study are consistent with Becker (2021) who reported weak correlations between body weight and tail length in Meat-master rams.…”
Section: Phenotypic Correlations Between Live Body Weight and Linear ...supporting
confidence: 89%
“…The obtained data from the current study may play an important role in designing correlations based on morphometric measurements of certain body parts and both live body weight and carcass weight. According to the present literature, many researchers have designed regression analyses to predict body weights or carcass weights and used many body measurements as an indicator (Bassano et al., 2003 ; Bene et al., 2007 ; Cam et al., 2010 ; Ofori et al., 2020 ; Rashijane et al., 2023 ). In designing new regression analyses, GLc, GLt, Bd, Calfactor and Talfactor could be reliable parameters to reflect reality.…”
Section: Discussionmentioning
confidence: 99%
“…applied a multivariate adaptive regression spline algorithm test to estimate the live body weights in Savannah goats. By looking at the body characteristics of hair goats, meat yield is correlated with live body weight and can be increased with selection (Rashijane et al., 2023 ; Tozlu Çelik & Oflaz, 2017 ). Selection studies based on the physical characteristics of hair goats can lead to an enhancement in meat production.…”
Section: Discussionmentioning
confidence: 99%